Improved High-Throughput Sequencing of the Human Oral Microbiome: From Illumina to PacBio. (11th December 2020) - Zhang, Jie; Su, Lingkai; Wang, Yuan; Deng, Shuli
Abstract : Background . A comprehensive understanding of the commensal microflora and its relation to health is essential for preventing and combating diseases. The aim of this study was to examine the structure of the oral microbiome by using different sequencing technologies. Material and Methods . Five preschool children with no symptoms of oral and systemic diseases were recruited. Samples of saliva were collected. A 468 bp insert size library was constructed on the MiSeq platform and then subjected to 300 bp paired-end sequencing. Libraries with longer insert sizes, including a full-length 16S rDNA gene, were sequenced on the PacBio RS II platform. Results . A total of 122.6 Mb of raw data, including 244, 967 high-quality sequences, were generated by the MiSeq platform, while 134.6 Mb of raw data, including 70, 030 high-quality reads, were generated by the PacBio RS II platform. Clustering of the unique sequences into OTUs at 3% dissimilarity resulted in an average of 225 OTUs on the MiSeq platform; however, the number of OTUs generated on the PacBio RS II platform was 449, far greater than the number of OTUs generated on the MiSeq platform. A total of 437 species belonging to 10 phyla and 60 genera were detected by the PacBio RS II platform, while 163 species belonging to 12 phyla and 72 genera were detected by the MiSeq platform. Conclusions . The oral microflora of healthy Chinese children were analyzed. Compared with traditional 16S rRNA sequencing technology, the PacBio system, despite providing a lower amount of clean data, surpassed the resolution of the MiSeq platform by improving the read length and annotating the nucleotide sequences at the species or strain level. This trial is registered with NCT02341352 .